Conferencia Clínico Patológica (CPC) : paciente previamente sana con insuficiencia respiratoria debida a neumonía intersticial (2013)
ABSTRACT: We present the case of a 40-year-old woman, with no remarkable past medical history, who was admitted to San Vicente Foundation University Hospital, in Medellín, Colombia; she complained of respiratory symptoms lasting 20 days. Interstitial pneumonia associated with AIDS was diagnosed, which progressed to respiratory failure that did not respond to therapy directed against the opportunistic infections that were identified. She finally developed multiorgan failure that caused death.